Do Traders Front-Run News? Evidence From Form 8-K Disclosures of Class Action Lawsuit Settlements - Nguyen, Doanh Zone; Vemala, Prasad (Journal of Accounting and Finance, 2023)
Using a novel and unique dataset of class action settlement announcements from Form 8-K disclosures as a proxy for private information, we tested whether traders front-run on the announcements and whether traders capture cumulative abnormal return (CAR) surrounding the disclosures. Although overall volume does rise, there is no statistically significant evidence of front-running Form 8-K disclosures and no CAR surrounding the disclosures. This study, nonetheless, contributes to the literature by providing further evidence from a new dataset of class action litigation settlements that there is no front-running of news. The findings contribute to the contrary – albeit less popular – collection of studies that show traders do not have access to private information upon which to exploit through front-running to capture CAR.